(untitled) ("Journal "U". Economy. Management. Finance.", 2019)
The article discusses the advantages and disadvantages of the introduction of electronic document management system in the state institution – the southern customs administration. This innovation undoubtedly affects the efficiency of each of the staff and the organization as a whole, which is an important factor in the functioning of the organization. In addition to the technology of implementation, the consequences of such a decision are analyzed, which are not only positive, but also negative.